Architecture for a large scale learning ecosystem - Pal, J. van der; Buiel, E.; Korteling, H.; Oprins, E. (Springer, 2025)
This paper presents a concept for an integral learning ecosystem for the Netherlands armed forces consisting of six components: learning content, didactics, people, technology, data, and policy and governance. The ecosystem is designed to enhance personalized learning and development by improving both effectiveness and efficiency. To facilitate the design of learning ecosystems, we propose a reference architecture tailored to the Netherlands armed forces. This paper also explores the implications of this architecture for Automated Instructional Systems (AIS), emphasizing the need for adaptability, standardization, and seamless integration with learning analytics. The continuous development of this learning ecosystem in The Netherlands may serve as a testcase for AIS platforms, providing further research and evaluation of their effectiveness in large-scale learning ecosystems.